Challenges and realities of the teaching role in functional diversity: Colombian school contexts: Challenges in inclusive education and teacher training - Larrota Medrano, Diana Karina; Uribe Rodríguez, Ana Fernanda (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Currently, the number of students with functional diversity who have entered the Colombian educational system is large, therefore, the nerve center of this educational revolution is to transform paradigms from a practical perspective. In addition to this, the teacher plays a fundamental role in inclusion. This research was aimed at identifying the challenges and realities of the teacher in Colombian school contexts. In this sense, it was proposed from a quantitative cut methodology with a non-experimental design of descriptive scope. Emphasizing that a school for all is not a utopia, it is a space of students and for students where a range of particularities and skills typical of a humane and egalitarian school freely converge.